Virtual Reality in Adaptive Learning: Identifying Learning Styles and Integration in Educational Apps - Divyadharshini, P.; Princi, R.; Subashini, G.; Moohambgai, B. (Journal of Technology Informatics and Engineering, 2025)
The increasing demand for personalized education in digital environments has highlighted the limitations of traditional, static learning methods. This study addresses the challenge of accommodating diverse learning preferences and emotional responses by leveraging Virtual Reality (VR) to create immersive, adaptive learning systems. The research focuses on designing a VR-based educational framework that integrates artificial intelligence to personalize instruction, monitor emotional states, and support ethical assessment. A primary goal is to identify how students' learning styles and emotional conditions influence their experience in VR, and how educational systems can adapt in real time to these factors. Key components of the proposed system include customizable AI tutors that resemble familiar figures to boost learner motivation, real-time emotion detection during virtual exams, and cognitive load management through adaptive content delivery. Methods involve tracking emotions through facial analysis, monitoring gaze, and providing physiological feedback to dynamically adjust test environments. The findings suggest that while VR enhances engagement and satisfaction, excessive sensory input can lead to cognitive strain, underscoring the importance of balanced immersion. The study contributes a novel, emotion-driven VR framework that combines personalization, gamification, and ethical monitoring. This integrated approach provides a foundation for inclusive, engaging, and effective virtual learning systems that align with individual learner needs and support academic integrity.